Quantum Learning pada Pendidikan Anak Usia Dini Studi atas Buku Edutainment Pendidikan Anak Usia Dini: Quantum Learning pada Pendidikan Anak Usia Dini - Ahmad Sofyan; Siti Murdianingsih (STIT Sirojul Falah Bogor, 2023)
Quantum Learning is Learning in the form of tips, instructions, strategies and the whole learning process that can sharpen understanding and memory, and make learning as a fun and useful process, quantum learning can be said as a learning model that emphasizes to provide meaningful benefits and also emphasizes on the level of enjoyment of students.Learning activities in Early Childhood is an activity that seeks to integrate students in an integrated manner by taking into account the learning environment factors, student characteristics, characteristics of the study area and various learning strategies, both delivery, management and organization of learning. In the Edutainment book of Early Childhood Education there are various types of edutainment models that can be applied to early childhood. One of them is by playing and singing. Playing is very important for early childhood becausetheirtime is a period or age of play. There is no reason not to consider playing activities as learning activities. There are three reasons that underlie the emergence of the concept ofedutainment: This positive feeling (happy / happy) will accelerate learning, while negative feelings such as sadness, fear, threatened, and feeling unable to slow down will slow down the learning process or even stop altogether. If someone is able to use his potential reasoning and emotions accurately,then it will make a jump in learning achievements that were not unexpected. If every learner can be motivated appropriately and taught in a way that respects their learning style and modality, then they will all be able to achieve optimal learning outcomes. Keyword : Quantum Learning, Early Childhood Education, Childhood Education Edutainment Book